2016
DOI: 10.11604/pamj.2016.23.165.8758
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adequate weekly reporting for disease surveillance data among health facilities in Nairobi County, Kenya, 2013

Abstract: IntroductionKenya adopted the Integrated Disease Surveillance and Response (IDSR) strategy in 1998 to strengthen disease surveillance and epidemic response. However, the goal of weekly surveillance reporting among health facilities has not been achieved. We conducted a cross-sectional study to determine the prevalence of adequate reporting and factors associated with IDSR reporting among health facilities in one Kenyan County.MethodsHealth facilities (public and private) were enrolled using stratified random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(94 citation statements)
references
References 11 publications
10
82
2
Order By: Relevance
“…Contrarily, the regional surveillance levels in Ghana took up the responsibility of reproducing and distributing reporting forms, hence reducing the burden to incur reproduction costs on the lower reporting levels [62]. In line with our study ndings on irregular reporting methods, inconsistent use of various reporting channels results to inaccuracies in the compiled surveillance reports [29,53]. Use of varied reporting channels especially at the health facility level hindered effective retrieval of previously reported PC-NTDs data with some of the health workers using paper-based reports while others transmitted reports using mobile phones.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Contrarily, the regional surveillance levels in Ghana took up the responsibility of reproducing and distributing reporting forms, hence reducing the burden to incur reproduction costs on the lower reporting levels [62]. In line with our study ndings on irregular reporting methods, inconsistent use of various reporting channels results to inaccuracies in the compiled surveillance reports [29,53]. Use of varied reporting channels especially at the health facility level hindered effective retrieval of previously reported PC-NTDs data with some of the health workers using paper-based reports while others transmitted reports using mobile phones.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, lack of simpli ed surveillance tools limits the overall performance of surveillance and response systems [40]. Other previous studies showed that availing the relevant reporting tools improved surveillance performance at the health facility level [29,46,60]. Further ndings from the current study demonstrated that lack of adequate reporting tools and training on proper reporting demotivated health workers engagement in the surveillance system [50].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This result is below the target of 80% given in the WHO IDSR. 16 It is also lower compared to the result of a study done in Ethiopia which that more than 80% of centres rendered malaria reports according to the IDSR system, and the study done at Jeddah which reported 86%. 12,17…”
Section: Discussionmentioning
confidence: 73%
“…Good data quality remains a challenge especially in low resource settings. Assessments of implementation of IDSR in African countries have identi ed data quality issues such as late reporting [11], incomplete reporting [12] and data inconsistencies across reporting levels [13]. However, repeated assessments, feedback, data management trainings appear to improve data quality over time.…”
Section: Introductionmentioning
confidence: 99%